Microsoft Office 2000 advanced course - Cable, Sandra (South-Western Educational, 2000)
With a completion time of 75+ hours, this text has lessons which contain objectives, step-by-step instructions, screen illustrations, tips, notes, Internet coverage, chapter summaries, end-of-chapter exercises, projects, and SCANS correlations. Integration of each software application is covered throughout the book. With the use of both the Introductory Course and this text, Expert certification for Microsoft Office is achieved